Hubungan Pemeliharaan Kesehatan Gigi terhadap Status Karies Gigi pada Anak Usia 6-12 Tahun - Emmy Yadina Br Ginting; Ayu Wulandari; Firman Firman; Irfan Maulana Syam (Jurnal Terapi Gigi dan Mulut, 2025)
Dental caries is a disease affecting the hard tissues of the teeth, including enamel, dentin, and cementum, caused by the activity of microorganisms that ferment carbohydrates. This process leads to demineralization of tooth structures and may progress to more severe damage if left untreated. Proper oral and dental health maintenance plays a crucial role in preventing dental caries, particularly among school-aged children. This study aimed to determine the relationship between oral health maintenance and dental caries status among children aged 6–12 years at the Department of Pedodontics, Dental and Oral Hospital of Hasanuddin University, Makassar. This study employed an analytical observational design with a cross-sectional approach involving 70 children, selected using a total sampling technique. Data on oral health maintenance were collected using a structured questionnaire, while dental caries status was assessed through clinical examination. Data were analyzed using univariate and bivariate methods. Normality testing using the Kolmogorov–Smirnov test indicated that the data were not normally distributed; therefore, Chi-Square and Wilcoxon tests were applied. The results showed that the majority of respondents had good oral health maintenance practices (57.14%); however, dental caries was found in all children examined. Statistical analysis revealed a significant relationship between oral health care and dental caries status (p < 0.05), as well as a significant difference between oral health care and caries-related knowledge (p < 0.05). In conclusion, oral and dental health maintenance is significantly associated with dental caries status among children aged 6–12 years, although good maintenance practices alone were not sufficient to prevent the occurrence of dental caries.